Enhanced photocatalytic and antibacterial activity of plasma-reduced silver nanoparticles. Issue 44 (10th July 2018) - Chandana, L.; Ghosal, P.; Shashidhar, T.; Subrahmanyam, Ch.
Abstract : A non-thermal atmospheric pressure plasma jet has been used for the green synthesis of highly dispersed colloidal silver nanoparticles. Abstract : A non-thermal atmospheric pressure plasma jet has been used for the green synthesis of highly dispersed colloidal silver nanoparticles. The reducing species such as hydrogen radicals and hydrated electrons are identified, and the change in the solution pH is studied during AgNP formation. The structural properties and size of the plasma-reduced silver nanoparticles are characterized via X-ray diffraction, ultraviolet-visible spectroscopy, fluorescence spectroscopy and transmission electron microscopy. The size of the colloidal AgNPs is tuned by adjusting the initial concentration of AgNO3 . The effect of terephthalic acid, a hydroxyl radical scavenger, on the reduction of Ag + ion is studied. The typical catalytic activity data indicate the better performance of the plasma-reduced colloidal Ag nanoparticles than that obtained from the chemical reduction method. The antibacterial activity of the plasma-reduced Ag nanoparticles also shows a better performance than that of the chemically reduced AgNPs, highlighting the potential of the plasma reduction approach for the synthesis of metal nanoparticles, which are stable even after 30 days without a stabilizing agent. Additionally, the effects of hydroxyl scavengers (isopropyl alcohol) and Fenton's reagent (Fe 2+ salt) on CV degradation are studied.